The gendered effects of rainfall on early childhood nutrition: Evidence from Papua New Guinea - Leight, Jessica; Mukerjee, Rishabh; Schmidt, Emily (International Food Policy Research Institute, 2025)
Rainfall fluctuations can significantly reduce welfare for poor rural households in low- and middle-income countries dependent on rainfed agriculture for consumption, and in some contexts these adverse effects may be borne disproportionately by vulnerable household members, particularly children and girls. We present new evidence around the effects of rainfall fluctuations on child anthropometric status in Papua New Guinea, an understudied context characterized by some of the highest stunting rates in the world. We show that negative fluctuations in rainfall within a 12-month period are associated with reduced household consumption (driven by reduced consumption of own-produced food). Moreover, when these fluctuations are observed in the first year of a child’s life, they lead to a reduction in height forage and weight-for-age (though no shift in stunting), but this effect is observed only for girls: boys seem to be protected from the adverse effects of rainfall fluctuations experienced in infancy.